2009
DOI: 10.12693/aphyspola.116.47
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Mn-Doped BiFeO3Nanoparticles

Abstract: BiFeO 3 is a multiferroic material showing antiferromagnetic ordering and ferroelectric behavior simultaneously. Here, Mn-doped BiFeO 3 nanoparticles were synthesized up to 10% of Mn composition by a sol-gel process. The samples showed high crystallinity with no secondary phase up to 2% of Mn doping. A phonon peak at 1250 cm −1 in undoped BiFeO 3 showed anomalous intensity enhancement in the magnetically ordered phase below T N = 643 K due to a spin-phonon coupling. This behavior was less pronounced in the Mn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The obtained temperature behavior in figure 1 with drastic changes at the two critical temperatures T N and T C due to a phonon coupling with the magnetic ordering and the structural phase transition, respectively, was measured in the phonon spectra of BiFeO 3 by Haumont et al [6] and Fukumura et al [7]. A similar phonon anomaly was observed near the Néel temperature T N in BFO thin films by Ramirez et al [26], in Mn-doped BFO nanoparticles by Fukumura et al [27] and in YbMnO 3 thin films by Fukumura et al [28]. This was interpreted by a coupling between the phonon and magnetic spin system.…”
Section: Numerical Results and Discussionmentioning
confidence: 55%
“…The obtained temperature behavior in figure 1 with drastic changes at the two critical temperatures T N and T C due to a phonon coupling with the magnetic ordering and the structural phase transition, respectively, was measured in the phonon spectra of BiFeO 3 by Haumont et al [6] and Fukumura et al [7]. A similar phonon anomaly was observed near the Néel temperature T N in BFO thin films by Ramirez et al [26], in Mn-doped BFO nanoparticles by Fukumura et al [27] and in YbMnO 3 thin films by Fukumura et al [28]. This was interpreted by a coupling between the phonon and magnetic spin system.…”
Section: Numerical Results and Discussionmentioning
confidence: 55%
“…An intense phonon mode is indeed evidenced at 622cm -1 . The origin of this phonon is not yet clear and may be connected to a Jahn-Taller distortion of the oxygen octahedral induced by the 5% iron (Fe) substitution by the manganese (Mn) [15,16]. The intensity for this mode decreases for SLs with shorter period and we observe the simultaneous appearance of another vibrational mode at 720cm -1 .…”
Section: Resultsmentioning
confidence: 70%
“…The purity of BFO was found to be time independent. Other studies were found that for sol-gel method, 600 °C calcination temperature with time of 2 h is enough for forming crystals of BiFeO 3 [67][68][69][70].…”
Section: Effect Of Calcination Timementioning
confidence: 99%
“…The study of the effect of stirring temperature was applied to part I. In comparison, of the results obtained from the effect of calcination temperature for preheating method (600 °C for 0.5 h) and with other researchers like Fukumura et al [68] (600 °C for 2 h), the effect of stirring temperature was conducted within the range of 20-80 °C at calcination temperature of 600 °C and calcination time of 0.5 h and 2 h in a comparative study. It was regarded that, there was an improvement in weight percentage of BiFeO 3 on change stirring temperature.…”
Section: Effect Of Stirring Temperaturementioning
confidence: 99%